Influence of Different Silica Nanoparticles on Drop Size Distributions in Agitated Liquid‐Liquid Systems1. Issue 11 (19th September 2019) - Röhl, Susanne; Hohl, Lena; Kempin, Maresa; Enders, Frauke; Jurtz, Nico; Kraume, Matthias
Abstract: The impact of different silica nanoparticles on rheology, interfacial tension and drop size distributions in liquid‐liquid systems is determined experimentally. The particles vary in wettability and specific surface area. In contrast to commonly used high‐energy devices for Pickering emulsion preparation, low energy input by stirring allows to quantify drop breakage and coalescence in steady state and dynamic conditions. The experiments can provide essential information for drop size model development in nanoparticle‐stabilized emulsions. Abstract : The impact of silica nanoparticle concentration, wettability and specific surface area on physical properties, dispersion and coalescence of o/w and w/o emulsions is investigated in stirred tanks. Drop size distributions in steady state and dynamic conditions are quantified with an endoscope measurement technique.